Polyurethane / carbon black / Cu composite conductive fiber and preparation method and application thereof
By adding sheet copper powder to the conductive fiber spinning liquid of polyurethane and carbon black, polyurethane/carbon black/Cu composite conductive fibers were prepared, which solved the increase in viscosity and poor conductivity of the spinning liquid caused by excessive addition of conductive materials. The problem has achieved efficient electrical conductivity improvement.
Patent Information
- Application Number
- CN202411559211.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the prior art, when preparing carbon black-based conductive fibers, excessive addition of conductive materials leads to an increase in the viscosity of the spinning liquid, resulting in problems such as clogging of spinning needles, complex operation and poor conductivity.
By adding sheet copper powder to the conductive fiber spinning liquid of polyurethane and carbon black, a polyurethane/carbon black/Cu composite conductive fiber spinning liquid is formed, and conductivity with reduced viscosity and improved conductivity is prepared by wet spinning technology. fiber.
The viscosity of the spinning liquid was successfully reduced, the complex spinning operation was solved, and the conductive performance was significantly improved, reaching 56.4S/m, which was better than many reported carbon black-based flexible stretchable conductive fibers.
Smart Images

Figure CN119411250A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional fiber preparation, and in particular to a polyurethane / carbon black / Cu composite conductive fiber and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid progress of science and technology and the continuous improvement of people's quality of life, consumers' demands have quietly shifted from traditional durable, fashionable and convenient to the pursuit of smart textiles that integrate self-generation, electromagnetic protection, motion tracking and wearable electric heating and health care functions. Driven by this trend, wearable flexible strain sensors have become a research hotspot in the fields of sports health monitoring, virtual reality experience, and human motion capture due to their unique ability to accurately convert the subtle deformation of fibers or yarns into electrical signals and realize real-time data collection and analysis through Bluetooth technology, attracting the attention and exploration of many scholars.
[0003] Currently, wet spinning technology has shown the advantages of simple process, excellent production efficiency and significant cost-effectiveness in the preparation of carbon black-based conductive fibers. However, in order to give conductive fibers better electrical conductivity, it is usually necessary to mix a higher concentration of conductive fillers into the elastic matrix. Although this method is effective, it is also accompanied by a series of challenges: the excessive addition of conductive materials significantly increases the viscosity of the spinning solution, which not only easily causes the clogging of the spinning needle, but also increases the complexity and energy consumption of the spinning operation. More importantly, the sharp increase in the viscosity of the spinning solution seriously hinders the uniform mixing of the spinning solution and the uniform dispersion of the conductive particles in the pre-spinning treatment stage. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a polyurethane / carbon black / Cu composite conductive fiber and a preparation method and application thereof. The present invention obtains a polyurethane / carbon black / Cu composite conductive fiber spinning solution by adding flaky copper powder to a polyurethane and carbon black conductive fiber spinning solution, and prepares a polyurethane / carbon black / Cu composite conductive fiber by means of a wet spinning technology. The preparation method of the present invention not only successfully reduces the viscosity of the polyurethane / carbon black / Cu composite conductive fiber spinning solution, solves the problems of spinning needle blockage and complicated spinning operation, but also significantly improves the conductivity of the polyurethane / carbon black / Cu composite conductive fiber.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first object of the present invention is to provide a method for preparing a polyurethane / carbon black / Cu composite conductive fiber, comprising the following steps:
[0007] The flaky copper powder is mixed with a polyurethane and carbon black conductive fiber spinning solution to obtain a polyurethane / carbon black / Cu composite conductive fiber spinning solution; wherein the flaky copper powder accounts for 2.5% to 20% of the mass of the polyurethane / carbon black / Cu composite conductive fiber spinning solution; when the content of the flaky copper powder is lower than 2.5%, the viscosity of the polyurethane / carbon black / Cu composite conductive fiber spinning solution is high, and the spinning resistance of the polyurethane / carbon black / Cu composite conductive fiber spinning solution is large; when the content of the flaky copper powder is higher than 20%, the viscosity-reducing effect of the flaky copper powder on the polyurethane and carbon black conductive fiber spinning solution is almost eliminated, resulting in the polyurethane / carbon black / Cu composite conductive fiber being easily broken.
[0008] The polyurethane / carbon black / Cu composite conductive fiber spinning solution is wet spun to obtain the polyurethane / carbon black / Cu composite conductive fiber; wherein, the addition of flaky copper powder transforms the sliding friction between particles in the polyurethane and carbon black conductive fiber spinning solution into rolling friction, thereby reducing the viscosity of the polyurethane and carbon black conductive fiber spinning solution, and at the same time connects the carbon black in the polyurethane and carbon black conductive fiber spinning solution, thereby improving the establishment of electron transmission channels.
[0009] Preferably, the polyurethane / carbon black conductive fiber spinning solution is prepared according to the following method:
[0010] The polyurethane is dissolved in a solvent to prepare a polyurethane spinning solution with a mass fraction of 15%; the 15% polyurethane spinning solution is mixed with carbon black to obtain a polyurethane / carbon black conductive fiber spinning solution.
[0011] Preferably, in the polyurethane / carbon black conductive fiber spinning solution, the mass of the carbon black accounts for 5% to 40% of the mass of the polyurethane in the 15% polyurethane spinning solution.
[0012] Preferably, in the preparation of the polyurethane / carbon black / Cu composite conductive fiber spinning solution, the mixing treatment is carried out by ultrasound; and the mixing treatment conditions are: ultrasound at 40° C. to 60° C. for 8 h to 20 h.
[0013] Preferably, the operation of wet spinning is: subjecting the polyurethane / carbon black / Cu composite conductive fiber spinning solution to wet stretching treatment to obtain the polyurethane / carbon black / Cu composite conductive fiber; and the conditions of the wet stretching treatment are: stretching at an extrusion rate of 40 mL / min to 120 mL / min, and a stretch ratio of 1.2 to 2.0.
[0014] Preferably, after the polyurethane / carbon black / Cu composite conductive fiber spinning solution is wet-stretched, it is also necessary to soak in water for 1h to 8h to allow the solvent to fully diffuse; then dry at 40°C to 60°C for 12h to 36h to remove the residual solvent in the polyurethane / carbon black / Cu composite conductive fiber.
[0015] Preferably, in the preparation of the polyurethane / carbon black conductive fiber spinning solution, the mixing treatment conditions are: stirring at 40° C. to 60° C. for 10 h to 36 h.
[0016] Preferably, the solvent is selected from one or both of N,N-dimethylformamide and dimethyl sulfoxide.
[0017] The second object of the present invention is to provide a polyurethane / carbon black / Cu composite conductive fiber prepared by the above preparation method.
[0018] The third object of the present invention is to provide the use of the above-mentioned polyurethane / carbon black / Cu composite conductive fiber in the preparation of fabrics.
[0019] Preferably, the application method is: two polyurethane / carbon black / Cu composite conductive fibers are combined into a weft yarn, and 20 / 2 polyester sewing thread is a warp yarn, which are interwoven to form a plain fabric.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention provides a method for preparing a polyurethane / carbon black / Cu composite conductive fiber, wherein the polyurethane / carbon black / Cu composite conductive fiber is named TPU / CB / Cu composite conductive fiber, a conductive fiber spinning solution of polyurethane and carbon black is named polyurethane / carbon black conductive fiber spinning solution, and the polyurethane / carbon black conductive fiber is named TPU / CB conductive fiber; flaky copper powder is ultrasonically mixed with the TPU / CB conductive fiber spinning solution to obtain a TPU / CB / Cu composite conductive fiber spinning solution that is uniformly dispersed and free of agglomeration precipitation; the flaky copper powder accounts for 1% of the polyurethane The ester / carbon black / Cu composite conductive fiber spinning solution is 2.5% to 20% of the mass; the TPU / CB / Cu composite conductive fiber spinning solution is wet-spun to obtain a TPU / CB / Cu composite conductive fiber with uniform size, highly uniform dispersion of carbon black and stable structure; wherein the introduction of flaky copper powder not only significantly reduces the viscosity of the TPU / CB / Cu composite conductive fiber spinning solution, but also establishes more conductive network pathways inside the TPU / CB / Cu composite conductive fiber, greatly improving the elasticity and conductivity of the TPU / CB / Cu composite conductive fiber. The preparation method of the present invention not only successfully reduces the viscosity of the TPU / CB / Cu composite conductive fiber spinning solution, solves the problems of spinning needle blockage and complicated spinning operation, but also significantly improves the conductive performance of the TPU / CB / Cu composite conductive fiber.
[0022] 2. The present invention provides a TPU / CB / Cu composite conductive fiber, which has excellent conductive properties. Due to the synergistic effect between carbon black and flaky copper powder, a denser conductive path is established inside the TPU / CB / Cu composite conductive fiber, which makes its higher conductivity reach 56.4S / m, which is significantly better than many reported carbon black-based flexible stretchable conductive fibers; in addition, the TPU / CB / Cu composite conductive fiber has good mechanical properties and strength, far exceeding similar products on the current market. During the stretching process, the carbon black and flaky copper powder inside the TPU / CB / Cu composite conductive fiber can establish a new conductive connection, ensuring that the TPU / CB / Cu composite conductive fiber can still maintain good conductive properties in a deformed state. At the same time, because the carbon black and flaky copper powder are tightly bound by the fiber network, the carbon black and flaky copper powder are effectively prevented from falling off, thereby giving the TPU / CB / Cu composite conductive fiber excellent durability and stability.
[0023] 3. The present invention also applies TPU / CB / Cu composite conductive fibers to prepare interwoven plain fabrics. The TPU / CB / Cu composite conductive fibers are used as wearable sensors to monitor changes in human body movements in real time, and the interwoven plain fabrics prepared therefrom are used as health-care electric heaters, which have the advantages of gentle heating and protecting the human body from burns. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 In the figure, a is the shear viscosity of the prepared TPU / CB conductive fiber spinning solution changing with the shear rate, and b is the optical image of the prepared TPU / CB conductive fiber spinning solution.
[0025] Figure 2 In the figure, a is the viscosity-shear rate curve of the prepared TPU / CB / Cu composite conductive fiber spinning solution; b is the viscosity comparison diagram of the prepared TPU / CB / Cu composite conductive fiber spinning solution at a shear rate of 0.1 rad / s.
[0026] Figure 3 The figure is a flow chart of the wet spinning process of the TPU / CB / Cu composite conductive fiber of the present invention.
[0027] Figure 4 In the figure, a is an electron microscope image of carbon black, b is an electron microscope image of flaky copper powder, c is an electron microscope image of the TPU / CB / Cu composite conductive fiber of Example 1, d is a distribution diagram of the C element, and e is a distribution diagram of the Cu element.
[0028] Figure 5Super depth of field optical images of TPU / CB conductive fibers with different carbon black contents prepared in the present invention and TPU / CB / Cu composite conductive fibers of Examples 1 to 6, wherein a is PU 15%, b is 5% CB, c is 10% CB, d is 20% CB, e is 30% CB, f is 35% CB, g is 40% CB, h is 2.5% Cu, i is 5% Cu, j is 7.5% Cu, k is 15% Cu, and l is 20% Cu.
[0029] Figure 6 These are the longitudinal super-depth-of-field optical images and the bending and knotting super-depth-of-field optical images of the TPU / CB / Cu composite conductive fibers of Example 4 of the present invention, wherein a is the longitudinal super-depth-of-field optical image of the TPU / CB / Cu composite conductive fibers of Example 4, b is the bending and knotting super-depth-of-field optical image of the TPU / CB / Cu composite conductive fibers of Example 4, c is the actual optical image of the winding upper roller of the TPU / CB / Cu composite conductive fibers of Example 4, and d is the optical image of the interwoven plain weave fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 and a super-depth-of-field local magnified image.
[0030] Figure 7 In the figure, a is the tensile stress-strain curve of the TPU / CB conductive fiber prepared by the present invention, b is the resistance-tensile strain curve of the TPU / CB conductive fiber prepared by the present invention, c is the conductivity diagram of the TPU / CB conductive fiber prepared by the present invention, d is the tensile stress-strain curve of the TPU / CB / Cu composite conductive fiber of Examples 1 to 6, e is the resistance-tensile strain curve of the TPU / CB / Cu composite conductive fiber of Examples 1 to 6, and f is the conductivity diagram of the TPU / CB / Cu composite conductive fiber of Examples 1 to 6.
[0031] Figure 8 In the figure, a is a schematic diagram of the distribution of conductive particles inside the TPU / CB conductive fiber prepared by the present invention after drawing, and b is a schematic diagram of the distribution of conductive particles inside the TPU / CB / Cu composite conductive fiber of Examples 1 to 6 before and after drawing.
[0032] Fig. 9 The resistance change rate curves of the TPU / CB conductive fiber prepared in the present invention and the TPU / CB / Cu composite conductive fiber of Examples 1 to 6 when stretched at the same stretching rate and a fixed deformation of 10%, wherein a is 30% CB, b is 35% CB, c is 40% CB, d is 2.5% Cu, e is 5% Cu, f is 7.5% Cu, h is 15% Cu, and i is 20% Cu.
[0033] Fig.104 is a graph showing the electrical fatigue stability performance test results of the TPU / CB / Cu composite conductive fiber of Example 4, a is a graph showing the resistance change performance of the TPU / CB / Cu composite conductive fiber of Example 4 at different stretching speeds, b is a graph showing the resistance change performance of the TPU / CB / Cu composite conductive fiber of Example 4 under different tensile deformations, c is a graph showing the resistance change of the TPU / CB / Cu composite conductive fiber of Example 4 under different bending states, d is a graph showing the resistance change of the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fiber of Example 4 after cyclic washing and drying, and e is a graph showing the performance of the TPU / CB / Cu composite conductive fiber strain sensor of Example 4 under cyclic stretching loading and unloading>10000 times.
[0034] Fig.11 This is a schematic diagram of the TPU / CB / Cu composite conductive fiber strain sensor of Example 4 attached to different parts for detecting human body movement.
[0035] Fig.12 4 is a graph showing the electric heating performance of the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4, wherein a is a graph showing the air permeability comparison between the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 and different ordinary fabrics, b is a graph showing the moisture permeability comparison between the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 and different ordinary fabrics; c is an optical graph showing the water contact angle of the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 at different times.
[0036] Fig.13 This is a curve diagram of surface temperature variation of the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 under different voltages.
[0037] Fig.14 This is a graph showing the relationship between the surface temperature of the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 and the applied voltage.
[0038] Fig.15 This is an infrared thermal imaging image of the surface temperature change of the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fiber of Example 4 under different voltages. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In the prior art, in order to give the conductive fiber better conductivity, it is usually necessary to mix a higher concentration of conductive fillers into the elastic matrix. However, the excessive addition of conductive materials significantly increases the viscosity of the spinning solution, which not only easily causes the problem of clogging of the spinning needle, but also increases the complexity and energy consumption of the spinning operation. More importantly, the sharp increase in the viscosity of the spinning solution seriously hinders the uniform mixing of the spinning solution and the uniform dispersion of the conductive particles in the pre-spinning treatment stage.
[0041] In view of the problems existing in the prior art, the present invention provides a method for preparing a polyurethane / carbon black / Cu composite conductive fiber, comprising the following steps: mixing flaky copper powder with a polyurethane and carbon black conductive fiber spinning solution to obtain a polyurethane / carbon black / Cu composite conductive fiber spinning solution; wherein the flaky copper powder accounts for 2.5% to 20% of the mass of the polyurethane / carbon black / Cu composite conductive fiber spinning solution; and wet spinning the polyurethane / carbon black / Cu composite conductive fiber spinning solution to obtain a polyurethane / carbon black / Cu composite conductive fiber; wherein the addition of the flaky copper powder converts the sliding friction between particles in the polyurethane and carbon black conductive fiber spinning solution into rolling friction, thereby reducing the viscosity of the polyurethane and carbon black conductive fiber spinning solution, and at the same time connects the independently distributed carbon black in the polyurethane and carbon black conductive fiber spinning solution, thereby improving the establishment of electron transmission channels.
[0042] Among them, the introduction of flaky copper powder not only significantly reduces the viscosity of the TPU / CB / Cu composite conductive fiber spinning solution, but also establishes more conductive network pathways inside the TPU / CB / Cu composite conductive fiber, greatly improving the elasticity and conductivity of the TPU / CB / Cu composite conductive fiber. The preparation method of the present invention not only successfully reduces the viscosity of the TPU / CB / Cu composite conductive fiber spinning solution, solves the problems of spinning needle blockage and complicated spinning operation, but also significantly improves the conductive performance of the TPU / CB / Cu composite conductive fiber.
[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0044] Select polyurethane / carbon black-35%, TPU / CB-35% and prepare according to the following steps:
[0045] First, N,N-dimethylformamide and polyurethane were added to a reagent bottle, heated and stirred at 60° C. for 2 h to completely and evenly dissolve them, and a polyurethane spinning solution with a mass fraction of 15% was prepared.
[0046] Then, a polyurethane spinning solution with a mass fraction of 15% was weighed, and carbon black equivalent to 35% of the mass of TPU particles was added to the polyurethane spinning solution with a mass fraction of 15%, and heated and stirred at 50°C for 24 hours to make the carbon black evenly dispersed in the polyurethane spinning solution with a mass fraction of 15%, to obtain TPU / CB conductive fiber spinning solution, recorded as polyurethane / carbon black-35%.
[0047] The polyurethane / carbon black-35% was named CB-35% conductive fiber spinning solution, and the TPU / CB / Cu composite conductive fiber spinning solution was prepared based on the CB-35% conductive fiber spinning solution, and the addition amount of the flake copper powder was screened. The wet spinning process flow chart of the TPU / CB / Cu composite conductive fiber is shown in the figure. Figure 3 shown.
[0048] Example 1
[0049] A preparation method of TPU / CB / Cu composite conductive fiber spinning includes the following steps:
[0050] S1. Add 2.5% flaky copper powder to the CB-35% conductive fiber spinning solution, heat and stir at 50°C for 12 hours, then ultrasonicate for 2 hours, then put the reagent bottle back into a 50°C magnetic stirring water bath and heat and stir for 12 hours to evenly disperse the flaky copper powder in the TPU / CB conductive fiber spinning solution to obtain a TPU / CB / Cu-2.5% composite conductive fiber spinning solution.
[0051] S2. Preparation of TPU / CB / Cu composite conductive fibers:
[0052] A 10 mL syringe was used to absorb the TPU / CB / Cu-2.5% spinning solution, and a 22G needle was used to adjust the extrusion rate to 80 mL / min. The TPU / CB / Cu-2.5% spinning solution was injected into a deionized water coagulation bath for wet drawing and then collected by a collecting roller. After being soaked in deionized water for 8 hours, it was dried at 60°C for 24 hours to obtain TPU / CB / Cu-2.5% composite conductive fiber, recorded as 2.5% Cu.
[0053] Example 2
[0054] A method for preparing a TPU / CB / Cu composite conductive fiber has the same preparation steps as those in Example 1, except that the amount of flaky copper powder added in S1 is 5%, thereby obtaining a TPU / CB / Cu-5% composite conductive fiber, which is recorded as 5%Cu.
[0055] Example 3
[0056] A method for preparing a TPU / CB / Cu composite conductive fiber has the same preparation steps as those in Example 1, except that the amount of flaky copper powder added in S1 is 7.5%, thereby obtaining a TPU / CB / Cu-7.5% composite conductive fiber, recorded as 7.5%Cu.
[0057] Example 4
[0058] A method for preparing a TPU / CB / Cu composite conductive fiber has the same preparation steps as those in Example 1, except that the amount of flaky copper powder added in S1 is 10%, and a TPU / CB / Cu-10% composite conductive fiber is obtained, which is recorded as 10% Cu.
[0059] Example 5
[0060] A method for preparing a TPU / CB / Cu composite conductive fiber has the same preparation steps as those in Example 1, except that the amount of flaky copper powder added in S1 is 15%, thereby obtaining a TPU / CB / Cu-15% composite conductive fiber, which is recorded as 15% Cu.
[0061] Example 6
[0062] A method for preparing a TPU / CB / Cu composite conductive fiber has the same preparation steps as those in Example 1, except that the amount of flaky copper powder added in S1 is 20%, and a TPU / CB / Cu-20% composite conductive fiber is obtained, which is recorded as 20% Cu.
[0063] In order to investigate the effect of the amount of carbon black added on the preparation of TPU / CB conductive fiber spinning solution, the amount of carbon black added was screened, as shown in the following technical scheme:
[0064] First, N,N-dimethylformamide and polyurethane were added to a reagent bottle, heated and stirred at 60° C. for 2 h to completely and evenly dissolve them, and a polyurethane spinning solution with a mass fraction of 15% was prepared.
[0065] Then, a polyurethane spinning solution with a mass fraction of 15% was weighed, and carbon black equivalent to 5%, 10%, 20%, 30%, 35% and 40% of the mass of the polyurethane was added to the polyurethane spinning solution with a mass fraction of 15%, respectively. The mixture was heated and stirred at 50°C for 24 hours to make the carbon black evenly dispersed in the polyurethane spinning solution with a mass fraction of 15%, and polyurethane / carbon black conductive fiber spinning solution, i.e., TPU / CB conductive fiber, was obtained, which were recorded as PU15%, CB-5%, CB-10%, CB-20%, CB-30%, CB-35% and CB-40%, respectively.
[0066] Example 7
[0067] The preparation of a TPU / CB / Cu composite conductive fiber spinning method is the same as the preparation steps of Example 1, except that the CB-35% conductive fiber spinning solution in step S1 is replaced by CB-30% conductive fiber spinning solution to obtain a TPU / CB / Cu composite conductive fiber.
[0068] Example 8
[0069] The preparation of a TPU / CB / Cu composite conductive fiber spinning method is the same as the preparation steps of Example 1, except that the CB-35% conductive fiber spinning solution in step S1 is replaced by CB-20% conductive fiber spinning solution to obtain a TPU / CB / Cu composite conductive fiber.
[0070] Example 9
[0071] The preparation of a TPU / CB / Cu composite conductive fiber spinning method is the same as the preparation steps of Example 1, except that the CB-35% conductive fiber spinning solution in step S1 is replaced by CB-10% conductive fiber spinning solution to obtain a TPU / CB / Cu composite conductive fiber.
[0072] Example 10
[0073] The preparation of a TPU / CB / Cu composite conductive fiber spinning method is the same as the preparation steps in Example 1, except that the CB-35% conductive fiber spinning solution in step S1 is replaced with a CB-5% conductive fiber spinning solution to obtain a TPU / CB / Cu composite conductive fiber.
[0074] Embodiment 11
[0075] The preparation of a TPU / CB / Cu composite conductive fiber spinning is the same as the preparation steps of Example 1, except that the CB-35% conductive fiber spinning solution in step S1 is replaced with CB-40% conductive fiber spinning solution to obtain TPU / CB / Cu composite conductive fiber. After testing, the breaking strength of the TPU / CB / Cu composite conductive fiber prepared in Example 11 is 4.9MPa, the elongation at break is 70.3%, and the conductivity is 142.3S / m, which is lower than the mechanical properties of the TPU / CB / Cu composite conductive fiber prepared in Example 1. Therefore, Examples 1-6 of the present invention select CB-35% conductive fiber spinning solution as the base to prepare TPU / CB / Cu composite conductive fiber spinning solution.
[0076] observe Figure 1It can be seen from a in that the viscosity of TPU / CB conductive fiber spinning solution increases rapidly with the increase of carbon black content. For PU15% without carbon black, the shear viscosity at 1rad / s is 2.2Pa·s. When the amount of carbon black added reaches 40%, that is, CB-40%, the viscosity of TPU / CB conductive fiber spinning solution increases sharply and reaches 1640Pa·s. Figure 1 It can be concluded from b in the figure that the CB-40% conductive fiber spinning solution has almost no fluidity. Figure 1 From a and b in the figure, it can be seen that the viscosity of the TPU / CB conductive fiber spinning solution decreases with the increase of shear rate, and has obvious shear thinning characteristics.
[0077] observe Figure 2 It can be seen from a in that the shear viscosity of the TPU / CB / Cu composite conductive fiber spinning solution gradually decreases with the increase of shear rate, showing an obvious shear thinning phenomenon; Figure 2 The results in b show that the viscosity at a shear rate of 0.1rad / s shows that the addition of flaky copper powder significantly reduces the viscosity of the TPU / CB / Cu composite conductive fiber spinning solution. Compared with the TPU / CB conductive fiber spinning solution without flaky copper powder, i.e., 35% CB, the initial viscosity of the TPU / CB / Cu composite conductive fiber spinning solution with flaky copper powder is reduced from 1800Pa·s to about 1200Pa·s, a decrease of 33.33%. This is because the addition of flaky copper powder destroys the hard friction between carbon black, converts the sliding friction between carbon black and flaky copper powder into rolling friction, and reduces the viscous resistance of the TPU / CB / Cu composite conductive fiber spinning solution under shear conditions.
[0078] observe Figure 4 a and b in the figure show that the carbon black has a high uniformity, the size of the flake copper powder is between 4μm and 46μm, and the thickness is between 0.22μm and 2.27μm. Figure 4 From d and e in Figure 3, it can be seen that the carbon black is evenly distributed inside the TPU / CB / Cu composite conductive fiber, and the distribution of Cu element is also relatively uniform.
[0079] observe Figure 5 From a, b, c, d, e, f, g, h, i, j, k and l in the figure, it can be concluded that with the gradual increase of the content of carbon black CB in the TPU / CB / Cu composite conductive fibers, the internal structure of the TPU / CB / Cu composite conductive fibers becomes tighter, and the cross-section of the TPU / CB / Cu composite conductive fibers changes from having obvious pores and voids to a tight solid structure.
[0080] observe Figure 6From a and b in the figure, it can be seen that the surface of TPU / CB / Cu composite conductive fiber is smooth, flat, uniform in thickness and soft. The mass-produced TPU / CB / Cu composite conductive fiber is wound on the upper roller as shown in the figure. Figure 6 As shown in c, the current laboratory production rate can reach 10.613m / min. Figure 6 It can be concluded that the smooth conductive plain fabric was woven by weaving TPU / CB / Cu composite conductive fiber as weft yarn and commercially available polyester yarn as warp yarn on a loom, and the fabric had good conductive properties.
[0081] observe Figure 7 It can be concluded from a that with the increase of carbon black content, the breaking strength of TPU / CB conductive fiber first decreases from 36.7MPa to 4.9MPa, then increases to 15.9MPa, and then decreases to 10.5MPa. The breaking elongation gradually decreases from 377.1% to 70.3% with the increase of carbon black content. In order to make TPU / CB / Cu composite conductive fiber reach the maximum elongation of human joints 100% and obtain highly conductive fibers, it is further determined that the carbon black content of TPU / CB conductive fiber spinning solution is 35%. In general, the breaking strength of TPU / CB conductive fiber decreases with the increase of carbon black. This is because the addition of carbon black destroys the hydrogen bonds formed between polyurethane segments, weakens the interaction force between the segments, and thus significantly reduces the breaking strength of TPU / CB conductive fiber. With the increase of carbon black content, the breaking strength of TPU / CB conductive fiber gradually increases. This is because carbon black plays a role of physical cross-linking in the TPU / CB conductive fiber network. The increase of carbon black addition makes the physical entanglement points gradually increase, which significantly improves the tensile strength of TPU / CB conductive fiber.
[0082] Figure 7 The absence of 5%, 10%, and 20% resistance change rate-time images in figure b is due to the fact that the amount added is too small. After the wet drawing step in the spinning process, the spacing between the carbon blacks is enlarged so that under the combined action of the electric field and thermal vibration, electrons cannot pass through the polyurethane interface to form a conductive path, ultimately causing the resistance to exceed the range and the resistance change cannot be measured.
[0083] observe Figure 7 It can be seen from the c in that the conductivity of TPU / CB conductive fiber increases exponentially with the increasing content of carbon black. Figure 7It can be concluded from the figure that the conductivity of TPU / CB / Cu composite conductive fiber increases with the increase of the amount of flaky copper powder added. Compared with the conductivity of TPU / CB conductive fiber of 29.3S / m, the conductivity of Cu10% is 56.4S / m, which is nearly doubled, indicating that the addition of trace flaky copper powder is beneficial to the substantial increase of the conductivity of TPU / CB / Cu composite conductive fiber. This is because the addition of flaky copper powder increases the conductive pathway inside the TPU / CB / Cu composite conductive fiber, so that the carbon black originally independently distributed in the TPU / CB / Cu composite conductive fiber matrix is connected, and the electrons can achieve long-range transport, thereby improving the conductivity. The conductivity of the obtained TPU / CB / Cu composite conductive fiber is not as high as that of metal fiber. This is because there are a large number of conductive interfaces between carbon black and polyurethane, and electrons need to overcome the obstacles of the interface to achieve transmission, so that the obtained TPU / CB / Cu composite conductive fiber does not achieve conductivity comparable to that of metal fiber. Combining the electrical conductivity and mechanical properties of TPU / CB / Cu composite conductive fibers and the rheological properties of TPU / CB / Cu composite conductive fiber spinning solution, it was found that Cu10% has the best comprehensive performance. It not only has a high electrical conductivity, but also the flaky copper powder has a significant viscosity reduction effect on the TPU / CB / Cu composite conductive fiber spinning solution. The spinning difficulty of TPU / CB / Cu composite conductive fiber spinning solution is low, the energy consumption is low, and the obtained Cu10% has relatively good tensile fracture properties, which can meet the use requirements of smart wearables.
[0084] observe Figure 7 It can be concluded from the figure that with the increase of the content of flaky copper powder, the breaking strength of TPU / CB / Cu composite conductive fiber slightly decreased from 15.87MPa to 12.3MPa but no significant change occurred, while the breaking elongation of TPU / CB / Cu composite conductive fiber gradually decreased from 121.86% to 74.6%. The reason why the breaking strength of TPU / CB / Cu composite conductive fiber did not decrease significantly here is that the size of the added flaky copper powder is significantly larger than the size of the polyurethane molecular chain, and the content of flaky copper powder is low, which has a weak effect on the interaction between molecular chains. The breaking elongation of TPU / CB / Cu composite conductive fiber depends on the ability of the internal chain entanglement and orientation of TPU / CB / Cu composite conductive fiber. Due to the addition of flaky copper powder, it plays an anchoring role in TPU / CB / Cu composite conductive fiber, making it difficult for the polyurethane molecules to return to the previous curled and entangled state due to stretching and orientation during spinning, resulting in a decrease in the breaking elongation of TPU / CB / Cu composite conductive fiber. Therefore, when the addition amount of flaky copper powder decreases, the mechanical properties of TPU / CB / Cu composite conductive fibers will decrease.
[0085] and Figure 7 Compared with the TPU / CB / Cu composite conductive fiber in Figure 7 The resistance change rate of the TPU / CB conductive fiber in b is only Figure 7 e and Figure 7 Half of the TPU / CB / Cu composite conductive fiber.
[0086] observe Figure 8 a and Figure 7 b in combination with Figure 7 b and Figure 7 The analysis in Figure 3 shows that the resistance of TPU / CB conductive fiber changes significantly with the increase of tensile strain, and the change spans an order of magnitude, indicating that after the TPU / CB conductive fiber is stretched, the distance between the conductive particles inside it increases significantly, resulting in a sharp increase in resistance. In contrast, although the resistance of TPU / CB / Cu composite conductive fiber also changes with the increase of tensile strain, this change is relatively small, and the resistance value always remains in the same order of magnitude. This is mainly because the addition of flaky copper powder establishes a connection in the matrix of TPU / CB / Cu composite conductive fiber, connecting the originally independently distributed carbon black in series. Due to the large size of the flaky copper powder, it can still maintain a conductive path even after being stretched, thereby slowing down the trend of the resistance rising sharply with the increase of tensile strain.
[0087] observe Fig. 9 From a, b, c, d, e, f, g, h and i in the figure, it can be concluded that under the same tensile rate with fixed deformation, the resistance change law of TPU / CB / Cu composite conductive fiber is consistent, and TPU / CB / Cu composite conductive fiber exhibits stable performance.
[0088] observe Fig.10 It can be concluded from a in that as the stretching rate increases, the resistance change rate is relatively stable and the graph remains almost unchanged. Therefore, it can be concluded that the TPU / CB / Cu composite conductive fiber of the present invention has relatively stable performance, and its resistance change is not affected by the stretching rate, which is helpful for later applications in motion detection and electric heating.
[0089] observe Fig.10 It can be seen from Figure b that as the tensile deformation increases from 1% to 40%, the resistance change rate increases from 2.8% to 70.5%, and the resistance change rate of the five cycles in each deformation remains consistent, further indicating the stability of the TPU / CB / Cu composite conductive fiber. Fig.10 The resistance of the TPU / CB / Cu composite conductive fiber is almost unchanged under different bending conditions, indicating that the TPU / CB / Cu composite conductive fiber is insensitive to natural bending. In order to meet the washing requirements during daily use, the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fiber of Example 4 was washed with cyclic water and then tested for its resistance change curve. Fig.10The resistance in d is almost unchanged after more than ten washing and drying cycles, indicating that the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fiber of Example 4 has excellent water-resistant performance. Fig.10 It can be concluded from the graph that 10% Cu exhibits high stability after 10,000 cycles, indicating that the 10% Cu of Example 4 has excellent durability and reliability. It is noted that there is a small peak during each stretching reciprocation, which is caused by the rebound hysteresis of the TPU / CB / Cu composite conductive fiber with a high copper powder addition during the stretching process. This phenomenon is caused by the pinning effect of the nanocarbon material limiting the movement recovery of the TPU chain segment.
[0090] Considering the mechanical tensile properties and electrical sensitivity of Cu10%, the interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 can be used for motion monitoring in the field of wearable electronics.
[0091] In order to monitor the motion monitoring performance of TPU / CB / Cu composite conductive fibers, 10% Cu was fixed on the four joints of the volunteers in the laboratory and connected to a digital bridge. During the volunteers' exercise, the resistance change was used to monitor the changes in human joint motion.
[0092] observe Fig.11 It is concluded that Cu10% can be used as a resistance sensor to detect the movement of the human body, including the movement and bending of fingers, wrists, elbows and knees. The movement of these parts can be easily detected by TPU / CB / Cu composite conductive fibers, and the data values in multiple repeated movement detections are uniform and stable, indicating that TPU / CB / Cu composite conductive fibers have high accuracy and stability.
[0093] Breathability reflects the ability of fabrics to exchange air with the surrounding atmosphere, and plays an important role in maintaining and managing the thermal and moisture balance of the human body surface microenvironment. Fabrics with poor breathability tend to generate heat on the contact surface, making the wearer feel stuffy and causing reduced human comfort. Fig.12 From a in FIG, it can be seen that the air permeability of the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fibers of Example 4 is 299.42 mm / s, which is between those of spandex fabric (865.94 mm / s), polyester fabric (269.67 mm / s), denim fabric (114.58 mm / s), and cotton fabric (82.707 mm / s), and is better than those of common polyester, denim, and cotton fabrics, indicating that the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fibers of Example 4 has good air permeability.
[0094] observe Fig.12The moisture permeability of the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fiber of Example 4 is 2624.96 g / m 2 24h, on spandex fabric (2706.15g / m 2 ·24h), polyester fabric (2875.86g / m 2 ·24h), denim fabric (2425.27g / m 2 ·24h), cotton fabric (2406.83g / m 2 ·24h). This shows that the interwoven plain fabric prepared by TPU / CB / Cu composite conductive fibers has good moisture permeability. In addition, since TPU / CB / Cu composite conductive fibers and polyester are both hydrophobic materials, the interwoven plain fabric prepared by TPU / CB / Cu composite conductive fibers in Example 4 has hydrophobicity.
[0095] observe Fig.12 It can be concluded from c that the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fibers of Example 4 is hydrophobic within 60 seconds, but due to the interwoven polyester sewing threads, water droplets can penetrate into the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fibers of Example 4 within 90 seconds.
[0096] In order to test the heating performance of the interwoven plain fabric prepared by TPU / CB / Cu composite conductive fibers, the present invention pastes conductive copper sheets at both ends of the interwoven plain fabric prepared by TPU / CB / Cu composite conductive fibers to connect to a DC voltage source, and uses an infrared thermal imaging camera to monitor the temperature change of the interwoven plain fabric prepared by TPU / CB / Cu composite conductive fibers in real time.
[0097] By applying different DC voltages (10-30V) to conduct electric heating tests, combined with Fig.13 and Fig.14It is concluded that under a DC voltage of 10V to 30V, the maximum temperature of the interwoven plain fabric prepared by TPU / CB / Cu composite conductive fibers gradually increases from 23°C (10V) to 38°C (30V), and its temperature increases with the increase of the applied DC voltage, and the heating and cooling processes are both slowly increasing and decreasing processes. Therefore, the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fibers of Example 4 will not cause burns due to a sudden rise in temperature during the use of electric heating, and has the characteristics of gentle heating and slow cooling. Experimental studies have shown that when the heating temperature of the electric heating element is higher than 60°C, the human body will feel irritation and pain, or even burn the skin in a very short time. If the heating temperature is only at a medium temperature between 44°C and 60°C, the human skin will not have a more obvious perception in a short time, but after long-term continuous contact with the heat source, it will cause progressive damage from the superficial dermis to the deep dermis and various layers of tissues of the human skin, and this low-temperature burn of the skin is irreversible. Therefore, scholars should pay more attention to the research on the heating temperature of electric heating components.
[0098] Fig.15 The infrared thermal imaging diagram of the surface temperature change of the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fiber of Example 4 under different voltages. As can be seen from the figure, as the heating voltage gradually increases, the maximum stable temperature that can be achieved by the interwoven plain fabric prepared by the TPU / CB / Cu composite conductive fiber of Example 4 by electric heating gradually increases, reaching 38°C at 30V.
[0099] The interwoven plain fabric prepared from the TPU / CB / Cu composite conductive fibers of Example 4 of the present invention has a maximum electric heating temperature of 38°C within the human body safety voltage, which can achieve the effect of electrically heated health care fabric while ensuring the human body voltage safety, while ensuring that the human body does not suffer from dangerous situations of burns or low-temperature burns.
[0100] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing polyurethane / carbon black / Cu composite conductive fiber, characterized in that: The following steps are involved: The flaky copper powder is mixed with a polyurethane and carbon black conductive fiber spinning solution to obtain a polyurethane / carbon black / Cu composite conductive fiber spinning solution; wherein the flaky copper powder accounts for 2.5% to 20% of the mass of the polyurethane / carbon black / Cu composite conductive fiber spinning solution; The polyurethane / carbon black / Cu composite conductive fiber spinning solution is wet-spinned to obtain the polyurethane / carbon black / Cu composite conductive fiber; Among them, the addition of flaky copper powder converts the sliding friction between particles in the conductive fiber spinning solution of polyurethane and carbon black into rolling friction, reduces the viscosity of the conductive fiber spinning solution of polyurethane and carbon black, and connects the independently distributed carbon black in the conductive fiber spinning solution of polyurethane and carbon black.
2. The method for preparing a polyurethane / carbon black / Cu composite conductive fiber according to claim 1, characterized in that: The polyurethane / carbon black conductive fiber spinning solution is prepared according to the following method: Dissolving polyurethane in a solvent to prepare a polyurethane spinning solution with a mass fraction of 15%; 15% of polyurethane spinning solution is mixed with carbon black to obtain polyurethane / carbon black conductive fiber spinning solution.
3. The method for preparing a polyurethane / carbon black / Cu composite conductive fiber according to claim 2, characterized in that: In the polyurethane / carbon black conductive fiber spinning solution, the mass of the carbon black accounts for 5% to 40% of the mass of the polyurethane in the 15% polyurethane spinning solution.
4. The method for preparing a polyurethane / carbon black / Cu composite conductive fiber according to claim 1, characterized in that: The mixing treatment is carried out by ultrasound; and the mixing treatment is carried out under the conditions of ultrasound at 40° C. to 60° C. for 8 h to 20 h.
5. The method for preparing a polyurethane / carbon black / Cu composite conductive fiber according to claim 1, characterized in that: The wet spinning operation is: subjecting the polyurethane / carbon black / Cu composite conductive fiber spinning solution to wet stretching treatment to obtain the polyurethane / carbon black / Cu composite conductive fiber; the wet stretching treatment conditions are: stretching at an extrusion rate of 40 mL / min to 120 mL / min, and a stretch ratio of 1.2 to 2.
0.
6. The method for preparing a polyurethane / carbon black / Cu composite conductive fiber according to claim 2, characterized in that: The mixing treatment conditions are: stirring at 40°C to 60°C for 10h to 36h.
7. The method for preparing a polyurethane / carbon black / Cu composite conductive fiber according to claim 2, characterized in that: The solvent is selected from one or both of N,N-dimethylformamide and dimethyl sulfoxide.
8. A polyurethane / carbon black / Cu composite conductive fiber obtained by the method for preparing the polyurethane / carbon black / Cu composite conductive fiber according to any one of claims 1 to 7.
9. Use of the polyurethane / carbon black / Cu composite conductive fiber according to claim 8 in preparing fabrics.
10. Use of the polyurethane / carbon black / Cu composite conductive fiber in preparing fabrics according to claim 9, characterized in that: The application method is as follows: two polyurethane / carbon black / Cu composite conductive fibers are combined into a weft yarn, and 20 / 2 polyester sewing thread is used as a warp yarn, which are interwoven to form a plain fabric.
Citation Information
Patent Citations
High-elasticity conductive fiber and preparation method thereof
CN102953137A
Preparation method of functional regeneration cellulose fiber
CN106381564A
Conductive yarn and preparation method thereof
CN115467035A
Polytetrafluoroethylene fibres and filaments having reduced electrical resistance
GB1384016A
Copper-containing monofilaments, their production and fishery material thereof
JP1985185811A
Cited By
High-elasticity self-adaptive conductive compensation fiber as well as preparation method and application thereof
CN122061263A